PROSES RANCANGAN RANGKA OVEN BATU BARA PADA PT. X - Sandy Suryady; Agung Dwi Sapto (Jurnal Ilmiah Teknik, 2023)
A coal oven is one of the important laboratory tools which has the following functions: To heat or dry laboratory equipment or other objects. In the process of making this oven, several processes are carried out using conventional machines. In the manufacturing process, various things such as: material selection, frame making, body installation, installation of heaters, panels and motors, finishing etc. The manufacturing process is a process of treating parts (components) using machines where objects are formed by removing or removing some of the material from the workpiece with the aim of obtaining workpieces (components) with good accuracy and high precision so as to produce quality and quality products. high according to the wishes and product standards. Before entering into the manufacturing process, the oven is still not shaped like anything.